Code-switching in an institutional setting: negotiating social roles in bilingual encounters in Guatemala - Choi, Jinsook (Círculo de Lingüística Aplicada a la Comunicación, 2014)
In this paper, I investigate the ways in which bilingual speakers utilize linguistic resources to negotiate social roles and manage social relationships at an institutional setting in Momostenango, Guatemala. Drawing from studies on code-switching and politeness, I examine the ways in which speakers utilize the available language resources—Spanish and K’iche’ on the one hand, and second-person pronouns on the other—to negotiate social roles in institutional interactions. This study contributes to our understanding of the ways in which bilinguals organize and conceptualize social roles in culturally specific and meaningful ways. The qualitative analysis of speech examples can adequately show facets of social life when combined with an ethnographic understanding. In addition, by focusing on actual language use and on a single institutional setting rather than multiple ones, this study brings to light the complex dynamics of using both Spanish and K’iche’ as well as formal and familiar pronouns in Guatemala.